Biomechanical report for the IAAF World Championships London 2017 long jump men's - Tucker, C.; Nicholson, G.; Cooke, M.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The aim of the long jump is simply to run as fast possible and to jump as high as possible from the take-off board. It demands strong legs for jumping from the board as well as being able to coordinate the movements of take-off, flight and landing. This report focussed on the crucial elements of the run-up (approach phase) and take-off. The velocities reached on the runway are similar to those of a sprinter (velocities in the men's final ranged from 9.91 - 10.82 m/s in the third-last and second-last steps) but, unlike the sprinter, the long jumper has to control their speed in approaching the take-off board and place their foot as accurately as possible on the take-off board. The development of high velocities, coupled with the short contact time of take-off (0.120 - 0.130 s) in the run up, means that the athletes' take-off angles will never reach the theoretical optimum angle for the longest possible range. Therefore, the take-off angles are much less that that (men's final range: 20.2° - 26.3°). The transition to from the approach phase (run-up) to take-off is probably one of the most important elements of long jumping technique. To jump the longest distance, the athlete must have a large horizontal velocity at the end of the run-up and the foot placed as accurately as possible on the take-off board. Most of the finalists, apart from Lapierre, used the typical strategy of a longer penultimate step and a shorter last step to prepare for take-off. Most athletes increased their step length between the third-last and second-last steps (mean increase 6%) whereas for the last step, there was a mean reduction in step length of 9%. Manyonga, the gold medallist, had the largest reduction in step length at 19% for the last step. This approach of a longer penultimate and shorter last step can lower the height of the centre of mass (CM) in the penultimate step and therefore allow the athlete to have a higher take-off height in the last step. Manyonga had one of the largest changes in step length and also had one of the largest CM lowering values (Table 9). This could be a deliberate strategy on the part of Manyonga to increase his CM height at take-off and thereby increase his vertical velocity without losing too much horizontal velocity at take-off. The purpose of the contact phase on the take-off board is to gain lift (vertical velocity) while retaining as much horizontal velocity as possible. It was interesting that second-placed Lawson had the largest value of 9.56 m/s for horizontal velocity at take-off yet the lowest vertical velocity (3.51 m/s) at this point. He also had the second lowest loss in horizontal velocity (1.10 m/s). Menkov only had one measured jump in the entire final and finished in an agonising fourth position. On the take-off board, he lost 8 centimetres which if he had reduced to 2 centimetres would have resulted in him getting the bronze medal. He lost the most velocity of any competitor on the board (2.8 m/s). His knee angular velocity (how quickly the knee angle reduced) was the second lowest of the finalists. This relatively slow movement in his standing leg may indicate a lack of eccentric strength necessary to prevent a loss in horizontal velocity while trying to increase vertical velocity. This phase on the take-off board may require development to ensure better, more accurate foot placement along with more explosive movement from it. He may well be regularly in contention for medals if this becomes consistently better. Shi, who finished in sixth place, had one of the largest vertical velocities at take-off and had the largest value for CM lowering. Again, a deliberate strategy to is possible here to increase take-off velocity in the vertical as he had a large knee range of motion (44.4°) from contacting the board to reaching his minimum knee position. However, this was coupled with a loss in horizontal velocity of 2.61 m/s on the take-off board so perhaps he needs to work more on trying to maintain this horizontal velocity on the board. Overall from this analysis, it is clear that high velocities in the run-up phase helps the athlete prepare for take-off. The transition to take-off is crucial and accurate placement of the take-off foot on the board can mean the difference between winning a medal and not (as in the case of Menkov).